Existential Transformative Coaching: Working With Images, Feelings And Values To Revitalize The Life-World (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
Coaching is often seen as a relatively short-term process focused on behavioural issues and goal-setting. In this article, we explore how an existential approach might be used to engage clients in the realms of image-work, feelings and values in order to uncover tacit knowledge and meaning that will encourage long-lasting and far-ranging change and new purpose. Case studies of transformative existential coaching work are presented as illustrative examples of how a coach might employ these techniques in practice.
Keywords: Coaching; transformative; imagery; imagination; emotion; feelings; values; creativity; dialogue